Frequency of needle stick injuries among healthcare providers during large-scale SARS-CoV-2 vaccination brigades - Moran-González, Jorge Daniel; Padilla-Orozco, Magaly; Guzman-Lopez, Abel; Ochoa-Bayona, Hilda Cristina; Camacho-Ortiz, Adrian (Frontiers in Public Health, 2023)
The frequency of needlestick-related accidents in large-scale vaccination brigades during the COVID-19 pandemic is unknown. We determined the incidence of needlestick injuries (NI) from the SARS-CoV-2 vaccination brigades in the Monterrey metropolitan area. We calculated the rate of NI by 100,000 doses administered from a registry of over 4 million doses.